Pharmacokinetic characterization of 2-(3-benzoyl)-4-hydroxy-1,1-dioxo-2H-1,2-benzothiazine-2-yl-1-phenylethanone, a novel 11β-hydroxysteroid dehydrogenase type 1 inhibitor in rats - Zheng, Zhi; Seo, Hyewon; Kwak, Hyun Jung; Kim, Ki Young; Ahn, Jin Hee; Bae, Myung Ae; Song, Jin Sook (Archives of pharmacal research, 2016)
11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is associated with metabolic syndromes such as type 2 diabetes mellitus and obesity. A new 11β-HSD1 inhibitor known as 2-(3-benzoyl)-4-hydroxy-1, 1-dioxo-2H-1, 2-benzothiazine-2-yl-1-phenylethanone (KR-66344) is being developed as a therapeutic agent for these metabolic diseases. The purpose of this study was to characterize the pharmacokinetics of KR-66344 to support further preclinical development. KR-66344 showed high liver microsomal stability with T 1/2 values >3 h and high permeability with apparent permeability coefficients of 15.2–24.2 × 10 −6 cm/s in Caco-2 cell monolayers. KR-66344 was also strongly bound to plasma proteins (>98 %). After intravenous dosing, KR-66344 exhibited low systemic clearance (0.27–0.37 L/h/kg) and a low to moderate volume of distribution at steady state (0.79–0.8 L/kg). The bioavailability and terminal half-lives of KR-66344 following oral administration were 25 % and 1.7–3.3 h, respectively. In addition, KR-66344 showed dose-independent pharmacokinetics at 0.5–10 mg/kg in intravenous and oral pharmacokinetic studies.